The m(6)A Reader ECT2 Controls Trichome Morphology by Affecting mRNA Stability in Arabidopsis - Wei, Lian-Huan (Plant Cell, 2018)
The epitranscriptomic mark N(6)-methyladenosine (m(6)A) can be written, read, and erased via the action of a complex network of proteins. m(6)A binding proteins read m(6)A marks and transduce their downstream regulatory effects by altering RNA metabolic processes. The characterization of m(6)A readers is an essential prerequisite for understanding the roles of m(6)A in plants, but the identities of m(6)A readers have been unclear. Here, we characterized the YTH-domain family protein ECT2 as an Arabidopsis thaliana m(6)A reader whose m(6)A binding function is required for normal trichome morphology. We developed the formaldehyde cross-linking and immunoprecipitation method to identify ECT2-RNA interaction sites at the transcriptome-wide level. This analysis demonstrated that ECT2 binding sites are strongly enriched in the 3′ untranslated regions (3′ UTRs) of target genes and led to the identification of a plant-specific m(6)A motif. Sequencing analysis suggested that ECT2 plays dual roles in regulating 3′ UTR processing in the nucleus and facilitating mRNA stability in the cytoplasm. Disruption of ECT2 accelerated the degradation of three ECT2 binding transcripts related to trichome morphogenesis, thereby affecting trichome branching. The results shed light on the underlying mechanisms of the roles of m(6)A in RNA metabolism, as well as plant development and physiology.